PEMANFAATAN DIGITAL GAME BASE LEARNING DENGAN MEDIA APLIKASI KAHOOT.IT UNTUK PENINGKATAN INTERAKSI PEMBELAJARAN - Vivi vinika elita Putri; Muhamad Abdul roziq Asrori (STKIP PGRI TULUNGAGUNG, 2022)
After the issuance of Minister of Education and Culture Regulation No. 23 of 2017 concerning School Day is a problem for students and teachers in the process of learning interaction, especially those with learning hours at the end of the day of learning. Generally students are exhausted and lack enthusiasm to follow the series of learning in class. In these crucial hours the teacher is required to be creative in order to manage the learning class well and effectively. The use of the digital game approach by utilizing the kahoot.it application is used to see the progress of learning interactions as they arise. This research uses a qualitative approach to the type of case study. Data were collected by means of observation and interviews with research informants who have been determined to accommodate the heterogeneous of the research subjects. Data analysis was performed by interactive data analysis, while triangulation and extension of observation were used to obtain valid data. The results showed that the use of kahoot.it as a game-based innovative learning media was able to arouse the enthusiasm of learning and increase student achievement. The kahoot.it application that can display competitive evaluation of learning designs student achievement and prestige in learning interactions